Effects of Dietary Supplement of Basil Extract on Biochemical and Immunological Parameters and Growth Performance in Oncorhynchus mykiss - Mohammad Foad Noorbakhsh; Mehran Ghaemi; Amin Gholamhosseini; Amir Ali Heidari (Aquaculture Nutrition)
Ocimum basilicum has antioxidant, anti-inflammatory, and antimicrobial effects. The present study was conducted to evaluate the effects of O. basilicum extract on growth yield, safety, and marinating physiologic functions of the rainbow trout. The fish were fed with food rations containing 0%, 1%, 2%, and 3% of basil extract. Basil extract, especially at 1% concentration food ration, significantly increased the growth parameters compared with the control group (p<0.05). The biochemical parameters of hepatic function, renal function, glucose, triglyceride, and cholesterol level were significantly reduced in the treatment groups compared with the control group (p<0.05). Feeding with basil extract led to a significant increase in Ig, lysozyme, and respiratory burst assay, with the most prominent elevation at 2% concentration food ration. The mucosal antibacterial activity was improved. The mortality rate after exposure to Yersinia ruckeri was lower in the treatment groups compared with the control group. The results of the present study suggest that adding 2% basil extract to the food rations of the fish may improve their physiologic function and growth yield and reinforce their immune system.